2010
DOI: 10.1016/j.jcrs.2010.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual performance with blue light–filtering and ultraviolet light–filtering intraocular lenses

Abstract: The yellow-tinted IOLs were equivalent to the clear IOLs in postoperative contrast sensitivity, visual acuity, and color perception under photopic conditions. Patients with yellow-tinted IOLs made statistically significantly more mistakes in the blue range under dim light than patients with clear IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
2
29
0
2
Order By: Relevance
“…Overall, there were no statistically significant differences between the 2 study groups. Our results are in accordance with the majority of previous clinical trials,35,36,40,41,59 which report comparable contrast sensitivity values under photopic lighting conditions in patients with yellow-tinted blue light-filtering and conventional UV light-filtering IOLs. There are few reports indicating potential advantages of one or the other IOL type (yellow-tinted IOL versus UV light-filtering IOL) at low and high spatial frequencies.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Overall, there were no statistically significant differences between the 2 study groups. Our results are in accordance with the majority of previous clinical trials,35,36,40,41,59 which report comparable contrast sensitivity values under photopic lighting conditions in patients with yellow-tinted blue light-filtering and conventional UV light-filtering IOLs. There are few reports indicating potential advantages of one or the other IOL type (yellow-tinted IOL versus UV light-filtering IOL) at low and high spatial frequencies.…”
supporting
confidence: 93%
“…Our results are consistent with those in the current literature, which reports comparable visual acuity data between yellow-tinted blue lightfiltering IOLs and clear IOLs that filter UV light only, indicating that the orange-tinted blue lightfiltering effect might also be minimal to clinically insignificant. 5,20,24,34,36,37,[39][40][41][42]47 This is not particularly surprising, especially in regard to photopic vision, which relies on 3 cone receptor types with overlapping sensitivity ranges and a maximum efficacy at approximately 555 nm. At this wavelength, the blue light-filtering IOL displayed transmittance rates of approximately 80%, comparable to that of a middleaged human lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of clinical trials report comparable results for yellow-tinted and UV light-filtering IOLs regarding visual acuity data 3,12,14,30,32,33 as well as contrast sensitivity values. 15,31,[34][35][36] Color perception testing mostly showed higher error scores with yellowtinted IOLs than with UV light-filtering IOLs, whereas in color discrimination, yellow-tinted IOLs usually performed better than UV-light filtering IOLs. 8,14,15,30,34,36 These findings are in accordance with those in a previous study by our group 22 that found a significantly lower blue-yellow foveal threshold in patients with a yellow-tinted IOL.…”
Section: Discussionmentioning
confidence: 99%
“…These include the potential side effects of blue light-filtering on contrast sensitivity, 4,6 color perception, 4,7-12 and even on circadian rhythm. 1 Several studies 2,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have evaluated the effect of a yellow IOL on color discrimination after cataract surgery. Most did not find a change in color vision after the implantation of this type of IOL.…”
mentioning
confidence: 99%